Physicochemical changes and resistant-starch content of extruded cornstarch with and without storage at refrigerator temperatures - Neder Suárez, David; Amaya Guerra, Carlos Abel; Quintero Ramos, Armando; Pérez Carrillo, Esther; Alanís Guzmán, María Guadalupe de Jesús; Báez González, Juan Gabriel; García Díaz, Carlos Leonel; Núñez González, María Adriana; Lardizábal Gutiérrez, Daniel; Jiménez Castro, Jorge (2016)
Effects of extrusion cooking and low-temperature storage on the physicochemical changes and resistant starch (RS) content in cornstarch were evaluated. The cornstarch was conditioned at 20%–40% moisture contents and extruded in the range 90–130 ◦C and at screw speeds in the range 200–360 rpm. The extrudates were stored at 4 ◦C for 120 h and then at room temperature. The water absorption, solubility index, RS content, viscoelastic, thermal, and microstructural properties of the extrudates were evaluated before and after storage. The extrusion temperature and moisture content significantly affected the physicochemical properties of the extrudates before and after storage. The RS content increased with increasing moisture content and extrusion temperature, and the viscoelastic and thermal properties showed related behaviors. Microscopic analysis showed that extrusion cooking damaged the native starch structure, producing gelatinization and retrogradation and forming RS. The starch containing 35% moisture and extruded at 120 ◦C and 320 rpm produced the most RS (1.13 g/100 g) after to storage at low temperature. Although the RS formation was low, the results suggest that extrusion cooking could be advantageous for RS production and application in the food industry since it is a pollution less, continuous process requiring only a short residence time.